Activation of nitriles by silver(I) N-heterocyclic carbenes: An efficient on-water synthesis of primary amides. Issue 18 (3rd May 2019) - Thirukovela, Narasimha Swamy; Balaboina, Ramesh; Kankala, Shravankumar; Vadde, Ravindhar; Vasam, Chandra Sekhar
Abstract: A first example of silver(I) N -heterocyclic carbene (Ag(I)-NHC) catalyzed on-water synthesis of primary amides by hydration of nitriles under mild reaction conditions is described. This organometallic catalytic system has excellent tolerance for various homo-aromatic, hetero-aromatic and aliphatic nitriles to afford primary amides in good yields in neat water. Graphical abstract: Image 1